Proteomics for Studying the Effects of Ketogenic Diet Against Lithium Chloride/Pilocarpine Induced Epilepsy in Rats - Zheng, Yu-qin; Jin, Mei-fang; Suo, Gui-hai; Wu, You-jia; Sun, Yu-xiao; Ni, Hong (Frontiers in Neuroscience, 2020)
The ketogenic diet (KD) demonstrates antiepileptogenic and neuroprotective efficacy, but the precise mechanisms are unclear. Here we explored the mechanism through systematic proteomics analysis of the lithium chloride-pilocarpine rat model. Sprague-Dawley rats (postnatal day 21, P21) were randomly divided into control (Ctr), seizure (SE), and KD treatment after seizure (SE + KD) groups. Tandem mass tag (TMT) labeling and liquid chromatography-tandem mass spectroscopy (LC-MS/MS) were utilized to assess changes in protein abundance in the hippocampus. A total of 5,564 proteins were identified, of which 110 showed a significant change in abundance between the SE and Ctr groups (18 upregulated and 92 downregulated), 278 between SE + KD and SE groups (218 upregulated and 60 downregulated), and 180 between Ctr and SE + KD groups (121 upregulated and 59 downregulated) (all p < 0.05). Seventy-nine proteins showing a significant change in abundance between SE and Ctr groups were reciprocally regulated in the SD + KD group compared to the SE group (i.e., the seizure-induced change was reversed by KD). Of these, five (dystrobrevin, centromere protein V, oxysterol-binding protein, tetraspanin-2, and progesterone receptor membrane component 2) were verified by parallel reaction monitoring. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that proteins of the synaptic vesicle cycle pathway were enriched both among proteins differing in abundance between SE and Ctr groups as well as between SE + KD and SE groups. This comprehensive proteomics analyze of KD-treated epilepsy by quantitative proteomics revealed novel molecular mechanisms of KD antiepileptogenic efficacy and potential treatment targets.